1994
DOI: 10.1002/jmri.1880040343
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoferritin: Characterization of a novel superparamagnetic MR contrast agent

Abstract: A protein-encaged superparamagnetic iron oxide has been developed and characterized by using horse spleen apoferritin as a novel bioreactive environment. The roughly spherical magnetoferritin molecules, 120 A in diameter, are composed of a monocrystalline maghemite or magnetite core 73 A +/- 14 in diameter. Except for the additional presence of iron-rich molecules of higher molecular weight, the appearance and molecular weight (450 kd) of magnetoferritin are identical to that of natural ferritin; the molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 162 publications
(114 citation statements)
references
References 32 publications
4
106
1
Order By: Relevance
“…It has been reported that the relaxivity greatly depends on the strength of the magnetic field used (Gossuin et al 2010). The r 2 /r 1 value obtained for the ascorbic acid coated iron oxide nanoparticles of size 5 nm is in agreement with that reported by Bulte et al (1994), for protein encapsulated magnetic core of size 7 nm.…”
Section: Resultssupporting
confidence: 89%
“…It has been reported that the relaxivity greatly depends on the strength of the magnetic field used (Gossuin et al 2010). The r 2 /r 1 value obtained for the ascorbic acid coated iron oxide nanoparticles of size 5 nm is in agreement with that reported by Bulte et al (1994), for protein encapsulated magnetic core of size 7 nm.…”
Section: Resultssupporting
confidence: 89%
“…Magnetoferritin was prepared as previously described [Meldrum et al, 1992;Bulte et aL, 1994]. Repeated increments of 115 Fe(II) ions per protein molecule, followed by stoichiometric amounts of oxidant, were added to the synthesis mixture to give a theoretical final loading of 2300 Fe atoms in each protein cavity.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…14 In other words, ferritin is only partly superparamagnetic, and the native ferritin protein is therefore a rather weak T 2 contrast agent. Replacing its native iron core with a synthetic paramagnetic core has proven to result in effective T 2 contrast agents both in vitro 40,41 and in vivo. 42 More sensitive detection methods using phase images for generating hyperintense (bright) contrast might improve the detection of specific FerrH contrast generation, as was proposed recently by Mills and Ahrens.…”
Section: Evaluation Of Ferritin As Mri Reporter Gene G Vande Velde Et Almentioning
confidence: 99%